Data mining using radial basis function neural networks - Fu, Xiuju. (2008)
There are many tools for data mining. Neural network is important in data mining due to its intuitional characteristics superior to other methods. The principles of neural networks are derived from the thinking pattern of the human brain. A neural network learns patterns form noisy data for generalization. In our work, the radial basis function network is employed.